Pemenuhan Hak atas Informasi Publik sebagai Tanggung Jawab Negara dalam Mewujudkan Good Governance - Adam Muhshi (University of Jember, 2018)
There are two legal issues proposed in this study, inter alia, the nature of the right to public information and state's responsibility for the fulfillment of the right to public information. This study uses legal research with statute and conceptual approaches. The results of this study shows that the right to public information becomes part of the human rights as guaranteed by the 1945 Constitution. Public information has become a logical consequence of the obligation of the state to account for the implementation of its government to the citizens as its main purpose is to ensure the accountability and credibility of public institutions through the provision of information and documents at the public request so that the principle of information disclosure is one component in the realization of good governance. As a constitutional right of citizens, it also shows that ‘a contrario’ the fulfillment of public information is the responsibility of the state. According to this view, the fulfillment of the right to public information is not only related to obligations, but the content must be true and provided openly and honestly. It concludes that the fulfillment of public information conducted openly and honestly will contribute to an attempt to realize good governance Keywords: Human Rights, Public Information, Good Governance